Inherent forms and the evolution of evolution. Issue 8 (5th August 2019) - Newman, Stuart A.
Abstract: John Bonner presented a provocative conjecture that the means by which organisms evolve has itself evolved. The elements of his postulated nonuniformitarianism in the essay under discussion—the emergence of sex, the enhanced selection pressures on larger multicellular forms—center on a presumed close mapping of genotypic to phenotypic change. A different view emerges from delving into earlier work of Bonner's in which he proposed the concept of "neutral phenotypes" and "neutral morphologies" allied to D'Arcy Thompson's analysis of physical determinants of form and studied the conditional elicitation of intrinsic organizational properties of cell aggregates in social amoebae. By comparing the shared and disparate mechanistic bases of morphogenesis and developmental outcomes in the embryos of metazoans (animals), closely related nonmetazoan holozoans, more distantly related dictyostelids, and very distantly related volvocine algae, I conclude, in agreement with Bonner's earlier proposals, that understanding the evolution of multicellular evolution requires knowledge of the inherent forms of diversifying lineages, and that the relevant causative factors extend beyond genes and adaptation to the physics of materials. Abstract : A portion of the tree of life, showing representative morphologies in disparate multicellular clades. Research Highlights: John Bonner founded evo–devo by drawing lessons from social amoebae for other multicellular systems. His concept of "neutral morphologies" challenged the standard emphasis on gradualist adaptation. This article provides a "physico‐genetics" update of the concept.